Nest Architecture, Colony Composition and Feeding Substrates of Nasutitermes coxipoensis (Isoptera, Termitidae, Nasutitermitinae) in Subtropical Biomes of Northeastern Argentina - Laffont, Enrique Rafael; Coronel, Juan Manuel; Godoy, María Celina; Torales, Gladys Josefina (Universidade Estadual de Feira de Santana, 2012)
The mound- building termite Nasutitermes coxipoensis is commonly found at subtropical environments of northeast Argentina. This study gives new data about its nest architecture, biology and nutritional habits, comparing these results with other populations of the species. The volume of the analyzed nests varied between 0.91 dm3 y 207.33 dm3 , a wider range than previously reported for N. coxipoensis. The external and internal characteristics of the nests were similar to descriptions from other sites although it was not possible to differentiate the royal cell. The societies were monogynic and the queens laid eggs throughout the year. The body length and weight of primary reproductives were reported. The presence of alates within the mounds was higher in October and November. Feeding substrates consumed by N. coxipoensis at these habitats are also reported.
Keywords: Isoptera; Termitidae; Nasutitermes; Argentina